Comparative analysis of the reinforcement of a traditional wood floor in collective housing. In depth development with cross laminated timber and concrete - F. Martínez Soriano; N. González Pericot; E. Martínez Sierra (Case Studies in Construction Materials, 2016)
The restoration of heritage buildings deserves innovative and sustainable solutions that prioritize reinforcement versus substitution. When considering materials to undertake the actions, wood and its derivatives such as cross-laminated timber (CLT) are an interesting option. The aim of this study is to conduct a comparative analysis of two constructive systems from a structural point of view. Both are mixed systems: concrete-wood and CLT-wood. The reference floor structure proposed to simulate a real situation is searched among the typology of existing floors described in different treaties from XVIII and XIX Centuries. After comparing the samples in terms of deformation, in fire situation, and considering the influence by load increases on the building foundations, the lightness of the mixed solution wood-CLT offers advantages as it makes the state of permanent loads very similar to the original state of loads of the building.